2015
DOI: 10.1007/s12031-015-0626-2
|View full text |Cite
|
Sign up to set email alerts
|

Acute Response of the Hippocampal Transcriptome Following Mild Traumatic Brain Injury After Controlled Cortical Impact in the Rat

Abstract: We have previously demonstrated that mild controlled cortical impact (mCCI) injury to rat cortex causes indirect, concussive injury to underlying hippocampus and other brain regions, providing a reproducible model for mild traumatic brain injury (mTBI) and its neurochemical, synaptic, and behavioral sequelae. Here, we extend a preliminary gene expression study of the hippocampus-specific events occurring after mCCI and identify 193 transcripts significantly upregulated, and 21 transcripts significantly downreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…The overall results of our system biology study provide evidence for the impact of TBI on core aspects of gene regulation, which offers critical mechanistic information at the molecular level and can be used as novel elements of diagnosis and treatment. Compared to previous genomic profiling studies of TBI (Von Gertten et al, 2005, Rojo et al, 2011, Samal et al, 2015, Redell et al, 2013, Lipponen et al, 2016), our study differs in the molecular features assessed (gene expression only in previous studies vs. the combination of epigenome, gene expression, and alternative splicing in the current study), network modeling approaches (literature-based networks in previous studies vs data-driven, tissue-specific networks used here), tissues, time points, and TBI severity, which offer unique mechanistic aspects of the TBI pathology.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The overall results of our system biology study provide evidence for the impact of TBI on core aspects of gene regulation, which offers critical mechanistic information at the molecular level and can be used as novel elements of diagnosis and treatment. Compared to previous genomic profiling studies of TBI (Von Gertten et al, 2005, Rojo et al, 2011, Samal et al, 2015, Redell et al, 2013, Lipponen et al, 2016), our study differs in the molecular features assessed (gene expression only in previous studies vs. the combination of epigenome, gene expression, and alternative splicing in the current study), network modeling approaches (literature-based networks in previous studies vs data-driven, tissue-specific networks used here), tissues, time points, and TBI severity, which offer unique mechanistic aspects of the TBI pathology.…”
Section: Discussionmentioning
confidence: 98%
“…1) focusing on the impact of concussive injury on fundamental gene regulatory mechanisms. Unlike previous studies based on microarrays (Von Gertten et al, 2005, Rojo et al, 2011, Samal et al, 2015, Redell et al, 2013) and more recently RNA sequencing (Lipponen et al, 2016) which have reported changes in gene expression in response to TBI, in the current study we leveraged the power of system biology to combine genome-wide transcriptome and DNA methylome analyses in the hippocampus (a main site of cognitive dysfunction in TBI pathology) with modern data-driven gene network modeling approaches, which allowed us to extract information about crucial gene regulatory mechanisms (expression level, alternative splicing, epigenetic regulation) underlying TBI pathogenesis and to model tissue-specific gene-gene interactions which have the power to predict essential regulatory points. Gene networks are graphical models that depict genes as nodes and connections (reflecting regulatory relations or interactions) between genes as edges.…”
Section: Introductionmentioning
confidence: 85%
“… a Sources: (Ravizza et al, 2001), b (Tang et al, 2002), c (Elliott et al, 2003), d (Wilson et al, 2005), e (Okamoto et al, 2010), f (Sakaida et al, 2013), g (Almeida-Suhett et al, 2014), h (Samal et al, 2015), i (Zamanian et al, 2012), j (Zhang et al, 2016), k (Rakhade et al, 2005), l (Boer et al, 2010), m (Beaumont et al, 2012) …”
Section: Figmentioning
confidence: 99%
“…Although inflammation and up-regulation of inflammatory cytokines is predominant in brain transcriptomic alterations after traumatism (Redell et al, 2013; Samal et al, 2015), to our knowledge, no cell-specific study has been carried out so far to examine gene profile modifications specifically in microglia/monocytes following TBI. There is thus a clear need for such analysis.…”
Section: Transcriptome Profiling Of Microglia In Neurodegenerative Comentioning
confidence: 99%